Implementasi Re-design Application Mobile MRT Jakarta Menggunakan Metode User Centered Design - Rahma Fahriyah, Diana; Ikasari, Diana; Widiastuti (Indonesian Society of Applied Science, 2024)
MRT Mobile Application is used to access information easily and quickly for MRT users, such as schedule information, routes, stations, fares, and other additional services. Based on observations and questionnaires regarding the MRT mobile application, users often experience difficulties or obstacles in interacting with the application interface. Starting with a complex interface, confusing navigation of features to difficulty finding the information you need quickly. This affects the use of the application and reduces the level of user satisfaction. Based on these conditions, it is necessary to redesign the user interface of this application to make it easier to use. This research uses User Centered Design (UCD) method with four phases, which is Understand Context of Use, Specify User Requirements, Design Solution, and Evaluation Against Requirements in analyzing the UI/UX design process of the MRT mobile application. In the design stage, UCD principles are used to integrate insights from user data into UI/UX design process based on results of questionnaire analysis. The final result of this research is a prototype design and user interface design for the MRT mobile application that meets the expectations of application users.